2021
DOI: 10.3390/molecules26247454
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Method for Phenolic Compounds Extraction from Medicinal Plant (Juniperus procera) and Phytochemicals Screening

Abstract: Juniperus procera is a natural source of bioactive compounds with the potential of antitumor, antimicrobial, insecticidal, antifungal, and antioxidant activities. An optimization method was developed for total phenolic content (TPC), total flavonoid content (TFC), and total tannin content (TTC) in leaf and seed extract of Juniperus procera. Organic solvents (methanol (99.8%), ethanol (99%), and acetone (99.5%)), and deionized water (DI) were used for extraction. The estimation of TPC, TFC, and TTC in plant mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The optimal solvent for extraction of phytochemical compounds from plant material might depend on the constituents that are to be isolated, and the part of the plant used. Solvents have shown a significant effect in the extraction of phenolic compounds [41]. Our results have shown that jakjak fruit is a good source of antioxidant compounds which are suitable to be used as dietary supplements.…”
Section: Phenolic Compounds Of Jakjak Fruitmentioning
confidence: 62%
“…The optimal solvent for extraction of phytochemical compounds from plant material might depend on the constituents that are to be isolated, and the part of the plant used. Solvents have shown a significant effect in the extraction of phenolic compounds [41]. Our results have shown that jakjak fruit is a good source of antioxidant compounds which are suitable to be used as dietary supplements.…”
Section: Phenolic Compounds Of Jakjak Fruitmentioning
confidence: 62%
“…The literature suggests that in humans, approximately 50% of phenotypic variation in metabolite levels is genetically induced, but heritability estimates vary across metabolite classes [ 43 ]. Compared to plants, which are protected against external stimuli by secondary metabolites [ 44 ], animals are exposed to more diverse environmental stimuli, such as living environment, diet, and drugs [ 45 , 46 ]. In our study, the heritability of peptides and nucleosides was higher than that of other metabolite classes in all four detection modes, this suggests their potential as biomarkers for genetic selection.…”
Section: Discussionmentioning
confidence: 99%
“…Once achieved, the addition of a solution of 100 µL of saturated Na 2 CO 3 and distilled water was continued to the mark of 5 mL. The solution mixture was homogenized by centrifugation, then allowed to stand for 40 minutes, then the absorbance was measured by UV-Vis spectrometry (Gurning et al 2021;Patra et al 2021;Salih et al 2021;Tandi et al 2021). Total tannin was determined equivalence with tannic acid as standard.…”
Section: Tannin Contentmentioning
confidence: 99%